EDUKASI DAN PENDAMPINGAN HUKUM TERKAIT PERLINDUNGAN PEREMPUAN DAN ANAK DI KOTA BAUBAU - Abdullah, La Ode Dedi; Tri Pratiwi, Endang; Abdullah, Rudi; Agustina, Wa Ode (Jurnal Pengabdian Masyarakat Berkarya, 2025)
Legal education and assistance related to the protection of women and children in Baubau City are crucial efforts to address issues of gender-based violence, child abuse, and legal inequality. This initiative aims to increase public awareness of legal rights, strengthen access to justice, and provide direct support for victims. Through community-based legal counseling, workshops, and mentoring programs, this activity seeks to empower vulnerable groups and encourage active participation from local stakeholders, including government agencies, NGOs, and religious leaders. The methods used include socialization, training, and the formation of support networks to ensure sustainability. Preliminary findings indicate a lack of public understanding of legal protections, as well as structural barriers in reporting cases. This program is expected to enhance legal literacy, reduce violence rates, and create a safer environment for women and children. Recommendations include strengthening inter-institutional collaboration and optimizing digital platforms for outreach.